88.2k views
0 votes
Simplify 5p2/5p3

a) p/4
b) 3p3
c) 1/p
d) 6/7p3

User Kylef
by
6.2k points

1 Answer

6 votes

To simplify the above expression, we can use the quotient rule.


(x^a)/(x^b) =x^(a-b)

By using the above property we can subtract the exponents of the same base.

First step is to simplify the above expression, cancel out 5 from both numerator and denominator. Therefore,


(5p^2)/(5p^3) =(p^2)/(p^3)

=
p^(2-3)

=
p^-1

=
(1)/(p)

Since
x^-1 = (1)/(x).

So, the correct choice is c) 1/p.

I hope this helps you!

User BijiDango
by
5.0k points